2017
DOI: 10.3389/fncel.2017.00215
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms Controlling Maturation of Serotonin Neuron Identity and Function

Abstract: The brain serotonin (5-hydroxytryptamine; 5-HT) system has been extensively studied for its role in normal physiology and behavior, as well as, neuropsychiatric disorders. The broad influence of 5-HT on brain function, is in part due to the vast connectivity pattern of 5-HT-producing neurons throughout the CNS. 5-HT neurons are born and terminally specified midway through embryogenesis, then enter a protracted period of maturation, where they functionally integrate into CNS circuitry and then are maintained th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 96 publications
(169 reference statements)
1
13
0
Order By: Relevance
“…4A), which encodes a key transcription factor controlling serotonergic identity (Hendricks et al, 1999). PET1 regulates transcription of Tph2, Sert and other components of serotonergic identity (Spencer and Deneris, 2017). As expected, we found that all neurons expressing Tph2 mRNA also expressed Pet1 mRNA ( Fig.…”
Section: Tph2/vglut3 Switching Occurs In Susceptible Rats Following Csupporting
confidence: 82%
“…4A), which encodes a key transcription factor controlling serotonergic identity (Hendricks et al, 1999). PET1 regulates transcription of Tph2, Sert and other components of serotonergic identity (Spencer and Deneris, 2017). As expected, we found that all neurons expressing Tph2 mRNA also expressed Pet1 mRNA ( Fig.…”
Section: Tph2/vglut3 Switching Occurs In Susceptible Rats Following Csupporting
confidence: 82%
“…''Terminal selector'' transcription factors determine the anatomic and functional properties of mature neuronal subpopulations by regulating ''terminal effector'' genes that, in turn, define the cytoarchitectural, electro-physiological, and functional properties of postmitotic, mature neurons (Hobert, 2008;Serrano-Saiz et al, 2018;Spencer and Deneris, 2017). The expression of terminal selectors is sustained over time by feed-forward, autoregulatory loops, through which, they activate their own promoters (Deneris and Hobert, 2014).…”
Section: Etv1 As a Determinant Of DL Fmn Fatementioning
confidence: 99%
“…Interestingly, FEV, a member of the highly conserved ETS family of transcription factors was a predicted upstream regulator in both 2 day and 4 week datasets. FEV/PET1 is a key regulator of serotonergic neuronal development in the CNS [37], and has recently been identified as having a key role in food-related behavioral state switching and satiety [38]. This may represent a novel pathway through which GCs regulate food intake in the ARC.…”
Section: Discussionmentioning
confidence: 99%